Peningkatan Literasi Jurnalistik melalui Pelatihan Penulisan Berita - Fatimah, Dede; Nurhadi, Zikri Fachrul (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: The purpose of this PkM activity was to enhance the understanding and skills in journalistic writing among students at SMK Negeri 2 Garut through news writing training. Through this training, students were expected to gain practical experience and develop a stronger grasp of journalistic principles. Additionally, the activity aimed to inspire students to explore potential careers in journalism and related fields. Methodology: The methodology included preparation, core, and final stages. The preparation stage involved surveys, obtaining permissions, and conducting interviews. The core stage consisted of a pre-test, material delivery, discussions, and a post-test. The final stage involved evaluation and presentation of the results. Results: The results showed a significant improvement in the students' understanding and skills in news writing. Post-test scores indicated a substantial increase in comprehension, with most students achieving scores above 75%, reflecting a high level of understanding and application of the journalistic principles taught. Conclusions: This journalism training has succeeded in improving students' understanding and skills in writing news objectively and in a structured manner. Through project-based methods, students not only gain journalism theory, but also practical experience that enriches their insight into the dynamics of the media industry. The success of this activity shows that practice-based learning can effectively build students' competence and readiness in facing the world of work in journalism and communication. Limitations: The study was limited by the short duration of the training and the small sample size of students involved, potentially affecting the depth of skill absorption. Despite these limitations, the study offered valuable insights and set the stage for future research with more extensive training periods and larger participant groups. Contribution: This research is useful in the fields of education and journalism, particularly in enhancing journalistic literacy among vocational high school students.